2008
DOI: 10.3727/096368908787648029
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effect of Extracellular Superoxide Dismutase (EC-SOD) Mouse Embryonic Fibroblast (MEF) on Collagen-Induced Arthritis (CIA) Mice

Abstract: Rheumatoid arthritis is a chronic inflammatory disease. The generation of reactive oxygen species (ROS) within an inflamed joint has been suggested as playing a significant pathogenic role. Extracellular superoxide dismutase (EC-SOD) is a major scavenger enzyme of ROS, which has received growing attention for its therapeutic potential. To investigate the therapeutic effect of EC-SOD in mice with collagen-induced arthritis (CIA), we used mouse embryonic fibroblast (MEF) of transgenic mice that overexpresses EC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It is believed to be involved in the cardiovascular disorders (Gongora et al 2006) and in lung diseases (Ganguly et al 2006). However, the involvement of SOD3 in the inflammation may be illustrated by the protective effect of SOD3 on the collagen-induced arthritis in mice (Yu et al 2008). The strong increase of SOD3 expression in the inflamed porcine colonic mucosa may suggest the protective process taking place in the dysenteric porcine colon.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed to be involved in the cardiovascular disorders (Gongora et al 2006) and in lung diseases (Ganguly et al 2006). However, the involvement of SOD3 in the inflammation may be illustrated by the protective effect of SOD3 on the collagen-induced arthritis in mice (Yu et al 2008). The strong increase of SOD3 expression in the inflamed porcine colonic mucosa may suggest the protective process taking place in the dysenteric porcine colon.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, engraftment of the EC-SOD transgenic mouse embryonic fibroblast repressed inflammatory cytokines and the CII-specific T cells (Yu et al, 2008). In this study, the transgenic mice over-expressed EC-SOD in joint tissue and this protein was located in the lining layer of the synovium and endotherial cells in the sub lining.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, it has already been shown that the transfer of EC-SOD transgenic mouse embryonic fibroblast (MEF) represses the inflammatory arthritis (Yu et al, 2008). However, there is a question whether the over expression of EC-SOD on arthritic joint could also suppress the progression of disease or not.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used pharmacologic inhibitors of calcineurin are cyclosporine and tacrolimus (48). Both drugs exhibit potent immunosuppressive activity and have been used in the treatment of many chronic inflammatory diseases, including RA (29). However, systemic administration of these drugs can produce significant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Age‐matched male DBA/1 mice (Charles River) and CABIN‐1–overexpressing mice were immunized with bovine type II collagen (CII; Chondrex) at 8–12 weeks of age, as previously described (29). Briefly, CII was dissolved at a concentration of 0.25% in 0.01 N acetic acid.…”
Section: Methodsmentioning
confidence: 99%